SOSIALISASI DALAM RANGKA MENUMBUHKAN KEWIRAUSAHAAN DIGITAL PADA SISWA DI SMA ISLAHIL ATHFAL KECAMATAN RUMAK KABUPATEN LOMBOK BARAT - Rini Yuliandari; Saepul Pahmi; Mia Kurniati (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The aim of service is to grow and develop an entrepreneurial spirit and provide understanding in carrying out entrepreneurship by conducting entrepreneurial outreach. This Community Service target is students who are in the third grade, and they will soon graduate from school. Namely at Islahil Athfal High School and the service team involved in this activity were 5 lecturers and 5 students. The method used in this community service activity is the lecture method which is supported by effective presentation techniques. Apart from that, the socialization activity for each material will be followed by a question-and-answer session and discussion which can take the form of a Focus Group Discussion (FGD), and also involve interactive educational games or games. In this socialization, the output target to be achieved is for partners to have understanding and knowledge about entrepreneurship and how to use digital technology in entrepreneurship. This is due to the fact that Generation Z at Islahil Athfal High School, most of whom are technologically literate, but their use is still limited to entertainment, online games and social media. In fact, if they can make maximum use of this technology, it can become a source of income. The results of this service activity show that participants gained understanding knowledge about digital marketing. This is proven by the high enthusiasm of the participants in taking part in this Community Service, which is reflected in the questions asked by the participants and their understanding of the actions that need to be taken after this counseling.